EFEKTIVITAS KETERAMPILAN MANAGERIAL KEPALA SEKOLAH DI SEKOLAH DASAR - Titin Yudhiati; Ngurah Ayu Nyoman Murniati; Noor Miyono (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2022)
Managerial skills of school principals are very important in determining the success of school management. The success of school management can certainly be seen from various aspects, one of which is in the management of teacher management. The purpose of this study was to determine the effectiveness or influence of the principal's managerial skills on the work motivation of elementary school teachers in Bringin District, Semarang Regency. This research is a quantitative research with research respondents are 100 teachers from 26 elementary schools in Bringin District, Semarang Regency. Data collection techniques using questionnaires and documentation. The results showed that the principal's managerial skills had a positive and significant effect on teacher work motivation. The test results obtained a regression coefficient of 0.282. This shows that the principal's managerial skills play an important role in increasing teacher work motivation. The higher the managerial skills of the principal will be followed by the higher work motivation of teachers. Conversely, the lower the principal's managerial skills and work culture will be followed by the lower work motivation of teachers.Keterampilan managerial kepala sekolah merupakan hal yang sangat menentukan keberhasilan pengelolaan sekolah. Keberhasilan pengelolaan sekolah tentu dapat dilihat dari berbagai aspek, salah satunya adalah dalam manajemen pengelolaan guru. Tujuan dari penelitian ini adalah untuk mengetahui efektifitas atau pengaruh keterampilan manajerial kepala sekolah terhadap motivasi kerja guru Sekolah Dasar di Kecamatan Bringin Kabupaten Semarang. Penelitian ini merupakan penelitian kuantitatif dengan responden penelitian adalah 100 guru dari 26 Sekolah Dasar di Kecamatan Bringin Kabupaten Semarang. Teknik pengumpulan data dengan menggunakan kuesioner dan dokumentasi. Hasil penelitian menunjukkan bahwa Keterampilan manajerial kepala sekolah berpengaruh positif dan signifikan terhadap motivasi kerja guru. Hasil pengujian diperoleh nilai koefisien regresi sebesar 0,282. Hal ini menunjukkan bahwa keterampilan manajerial kepala sekolah berperan penting dalam peningkatan motivasi kerja guru. Semakin tinggi keterampilan manajerial kepala sekolah akan diikuti dengan semakin tingginya motivasi kerja guru. Sebaliknya, semakin rendah keterampilan manajerial kepala sekolah dan budaya kerja akan diikuti dengan semakin rendahnya motivasi kerja guru.